RETRACTED: Pengaruh Senam SKJ 2008 Terhadap Kebugaran Jasmani Siswi Sekolah Dasar Negeri 20 Alang Laweh Padang Selatan Kota Padang - Lusi Oktaviani; Arfon Meirony (Journal Sport Area, 2017)
This article has been withdrawn at the request of the Chief Editor. The reason for the withdrawal is that this article also published in the Jornal of Education Research and Evaluation.